The Need for Multi-Sectoral Partnerships in the Healthcare of Islamic Developing Countries During the Coronavirus Pandemic - Mahdieh Motamedi; Reza Vaezi; Seyed Mehdi Alvani; Davood Daneshjafari (Shahid Sadoughi University of Medical Sciences, 2021)
Nowadays, the field of healthcare is facing difficult issues in a way that both public and private sectors are fully aware of their inability to address emerging public health-related issues without the help of the other sector. Accordingly, public-private partnerships are put on the agenda in policy-related issues as a mechanism of cooperation between the public and private sectors to take into account the interests of both parties in the related contracts .From the late of 2019, the world is struggling with a new virus called the coronavirus, which has already cost a lot to the health sector. The partnership between the government and the private sector is very important to get through the corona period since the government alone cannot be responsible for the negative effects of the virus in the field of health. Considering the successes and failures of countries in the implementation of partnership models, a question arises as to how such partnerships for health development strategies can be attractive and effective in developing Islamic countries. In addition to the review of theoretical foundations of the subject and examining the development process of public-private partnerships, the study emphasizes the use of the third sector capacities. It further reviews the endowments and charitable affairs in the framework of multi-sectoral partnerships to develop health in the community with all available potentiality. The theoretical framework of the research includes the four steps of policy-making in the country, creating common perspectives among stakeholders, ensuring key success factors in the project, and reviewing the achievements of participation are considered. These policies are described after classifying and reconstructing the components in the research literature